The Development Of Moral Education In Malaysia - Balakrishnan, Vishalache (Penerbit Universiti Sains Malaysia, 2010)
Moral Education (ME) has been employed in the Malaysian education system for more than two decades. Policies have changed, and syllabi have been reviewed. The many challenges faced by makers, educators and students of ME have been analysed and evaluated continuously. In this article, the writer explains that Malaysia has come a long way where ME is concerned. The historical, religious and sociocultural aspects of Malaysia have been of concern since the first ME syllabus was constructed. The ME syllabus was revisited a decade ago, and now it might undergo another evaluation and revision. In-depth research needs to be done to ensure that ME in Malaysia is unique and dynamic within a multicultural setting.